Cognitive Change across Cognitive-Behavioral and Light Therapy Treatments for Seasonal Affective Disorder: What Accounts for Clinical Status the Next Winter? - Evans, Maggie (2013)
Efficacious treatments for seasonal affective disorder include light therapy and a seasonal affective disorder-tailored form of cognitive-behavioral therapy. Using data from a parent clinical trial, these secondary analyses examined the relationship between cognitive change over treatment with cognitive-behavioral therapy, light therapy, or combination treatment and mood outcomes the next winter. Sixty-nine participants were randomly assigned to 6-weeks of cognitive-behavioral therapy, light therapy, or combination treatment. Cognitive constructs (i.e., dysfunctional attitudes, negative automatic thoughts, and rumination) were assessed at pre- and post-treatment. Dysfunctional attitudes, negative automatic thoughts, and rumination improved over acute treatment, regardless of modality; however, in participants randomized to solo cognitive-behavioral therapy, a greater degree of improvement in dysfunctional attitudes and automatic thoughts was uniquely associated with less severe depressive symptoms the next winter. Change in maladaptive thoughts during acute treatment appears mechanistic of solo cognitive-behavioral therapy’s enduring effects the next winter, but is simply a consequence of diminished depression in light therapy and combination treatment.